Surface Acoustic Wave Device with Reduced Insertion Loss by Electrospinning P(VDF–TrFE)/ZnO Nanocomposites - Augustine, Robin; Sarry, Frederic; Kalarikkal, Nandakumar; Thomas, Sabu; Badie, Laurent; Rouxel, Didier (Nano-Micro Letters, 2016)
Surface acoustic wave (SAW) devices have been utilized for the sensing of chemical and biological phenomena in microscale for the past few decades. In this study, SAW device was fabricated by electrospinning poly(vinylidenefluoride-co-trifluoroethylene) (P(VDF−TrFE)) incorporated with zinc oxide (ZnO) nanoparticles over the delay line area of the SAW device. The morphology, composition, and crystallinity of P(VDF−TrFE)/ZnO nanocomposites were investigated. After measurement of SAW frequency response, it was found that the insertion loss of the SAW devices incorporated with ZnO nanoparticles was much less than that of the neat polymer-deposited device. The fabricated device was expected to be used in acoustic biosensors to detect and quantify the cell proliferation in cell culture systems.